Penggunaan Model Pembelajaran Inquiry untuk Meningkatkan Keterampilan Menyimak Wacana Tulis pada Siswa SMA Negeri 2 Gowa: The Use of Inquiry Learning Model to Improve Listening Skills of Written Discourse in Students of SMA Negeri 2 Gowa - Agusriyanto, Agusriyanto; Rabiah, Sitti; Mansyur, Umar (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to improve students' listening skills through the Inquiry learning model on the learning material of explanatory texts for class XI MIPA 6 SMAN 2 Gowa. Students' listening skills in explanatory texts are still very low because students are less interested in learning and do not understand the explanatory texts in more depth. The use of models and media that are less interesting makes students bored. This type of research is Classroom Action Research (CAR) which aims to improve the quality or problem solving in the subjects studied and observe the level of success or the consequences of their actions, to then receive additional actions which are improvements to the action. In the pre-cycle, the average student score was 31 and 1 student or 2% achieved the KKM. In cycle 1, the average student score was 51 and 3 students or 8% achieved the KKM. The average student score in cycle 2 increased by 81 and 30 students or 83% achieved the KKM. Based on the results of the research and discussion above, it can be concluded that the use of the Inquiry model can improve the listening skills of class XI MIPA 6 SMAN 2 Gowa students. Research data conducted during the pre-cycle stage to cycle 2 showed different results. Each cycle showed an increase in student learning outcomes.